Recent advances in the extraction, purification, structural-property correlations, and antiobesity mechanism of traditional Chinese medicine-derived polysaccharides: a review - Zhi, Nannan; Chang, Xiangwei; Wang, Xinrui; Guo, Jian; Chen, Juan; Gui, Shuangying (Frontiers in Nutrition, 2024)
Traditional Chinese medicine (TCM) has displayed preventive and therapeutic effects on many complex diseases. As natural biological macromolecules, TCM-derived antiobesogenic polysaccharides (TCMPOs) exhibit notable weight-loss effects and are seen to be a viable tactic in the fight against obesity. Current studies demonstrate that the antiobesity activity of TCMPOs is closely related to their structural characteristics, which could be affected by the extraction and purification methods. Therefore, the extraction, purification and structural-property correlations of TCMPOs were discussed. Investigation of the antiobesity mechanism of TCMPOs is also essential for their improved application. Herein, the possible antiobesity mechanisms of TCMPOs are systematically summarized: (1) modulation of appetite and satiety effects, (2) suppression of fat absorption and synthesis, (3) alteration of the gut microbiota and their metabolites, and (4) protection of intestinal barriers. This collated information could provide some insights and offer a new therapeutic approach for the management and prevention of obesity.